A superior technology to control Banana Xanthomonas Wilt (BXW) in Rwanda - Rietveld, Anne M.; Dusingizimana, P.; Blomme, Guy; Gaidashova, S.V.; Ocimati, W.; Ntamwira, J. (International Potato Center, 2020)
In this brief we discuss a new and promising technology to control xanthomonas wilt of banana, commonly referred to as BXW. We describe why this disease is a threat and what has been done to control it in the past. We also present evidence on an alternative technology to control BXW called Single Diseased Stem Removal (SDSR) and explain how we can make this technology accessible to Rwandese banana farmers.